Characterizing country-specific human and ecosystem health impact and damage cost of agricultural pesticides: the case for Thailand - Mankong P. (2023)
Purpose: Existing emission and toxicity characterization models in life cycle assessment are currently not suitable for assessing pesticide-related impacts of crop cultivation in tropical regions. This study aims to parameterize the scientific consensus model USEtox for Thai environments to derive toxicity characterization factors of pesticide emissions from agricultural systems in Thailand. Potential human toxicity and ecotoxicity impacts and related damage costs of pesticides used on nine crops cultivated in Thailand are quantified. Methods: Considering country-specific conditions, USEtox was adapted by applying the landscape and consumption parameters specific to Thailand. Related Thai-specific characterization factors of identified pesticides used in Thai agriculture were quantified. Four emission inventory models were applied to determine pesticide emission fractions in different environmental compartments. The consistent combination of pesticide emission mass and associated characterization factors yielded potential toxicity impact scores. Pesticide impact-related damage costs (external costs) on human health and ecosystem quality were quantified using valuation factors for Thailand. The crops with the highest total damage costs were selected and compared with the annual net incomes of the respective crop production systems. Results and discussion: Pesticide toxicity impacts assessed by using Thai-specific factors were different from the use of global average factors ranging from 1 to 169% (human toxicity) and from 0.1 to 3587% (ecotoxicity). Our results indicated the variability in impact scores influenced by emission modeling choices. Following PestLCI consensus emission estimation model, mango cultivation showed the highest human toxicity impacts of 0.07 DALY/ha, resulting in high human health damage costs mainly caused by Propineb (93%). Rice cultivation with a dry direct-seeded system exhibited the highest ecotoxicity impacts (3934 PDF m3 day/ha) and associated damage costs mainly caused by Oxadiazon (92%). Pesticides used in cultivation of nine crops resulted in total damage costs of 7188 and 3.01 million THB/crop-year for human health and ecotoxicity, respectively. Mango and rice production accounted for 70% and 17% of the total damage costs, which were 36% and 20% of the respective crops’ annual net income. Conclusions: Our study illustrates the ranking of pesticides applied throughout the crop calendar causing toxicological impact and related damage costs on human health and ecosystem quality. This helps identify crops and the main contributors to pesticide-related toxicity impacts in Thailand. Our study highlights the need for proper emission quantification and for the use of characterization factors locally parameterized to increase accuracy. Our results will be useful for future improvement toward more sustainable pesticide use. Graphical abstract: [Figure not available: see fulltext.]